2 - Développement rural au Cameroun: Et si les paysans le concevaient autrement? by Nyemba Ambela Jean - Nyemba Ambela Jean (Africa Development, 1992)
There is a fundamental divergence between state initiated rural development projects and the vision of development by the peasantry. For the latter development means the well-being of people in harmony with the natural and social environment. As a country wide study of Cameroon underscores, thus far , most development projects in Africa have failed to sustain such a harmony. Irrespective of the strategies employed and the degree of success or failure , the net results are the same : destruction of the production and the modes of reproduction of rural communities and pauperization of the peasantry. Presently , the systematic withdrawal of the state as a response to the crisis has exacerbated these problems. It is impossible to do without agriculture but it is not the only investment priority. Thus the question that ought to be addressed is what type of rural development for Africa of the 21st century ?